1997
DOI: 10.3109/13816819709041437
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental retardation in patients with hereditary retinoblastoma

Abstract: Dear Editor, We evaluated the cumulative incidence of mental retardation in patients with hereditary retinoblastoma. Records of the national Dutch retinoblastoma register were used. This register is complete from 1945 through 1994. Cooperation of the hereditary retinoblastoma patients or their parents was solicited by a letter from the ophthalmologist. The patients with hereditary retinoblastoma born between 1945 and 1970 were visited at home in 1985.' On that occasion, information on mental retardation was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…[1][2][3] These reports, in combination with large epidemiologic studies performed in Norway and Denmark, suggest an association between RB and Down syndrome. There have also been several studies demonstrating that children with Down syndrome experience more side effects from chemotherapy than children without Down syndrome.…”
Section: Discussionmentioning
confidence: 81%
“…[1][2][3] These reports, in combination with large epidemiologic studies performed in Norway and Denmark, suggest an association between RB and Down syndrome. There have also been several studies demonstrating that children with Down syndrome experience more side effects from chemotherapy than children without Down syndrome.…”
Section: Discussionmentioning
confidence: 81%
“…First, Windham et al (25) in an epidemiologic study on cancer linked to twining and to congenital malformations or low birth weight in Norway found a "higher rate of retinoblastoma based on only one case" for children with DS. Third, Moll et al (30,31) found two patients with DS in the Dutch Retinoblastoma Register among 241 cases of hereditary retinoblastoma and concluded that "hereditary retinoblastoma patients may have an increased risk for Down syndrome". Third, Moll et al (30,31) found two patients with DS in the Dutch Retinoblastoma Register among 241 cases of hereditary retinoblastoma and concluded that "hereditary retinoblastoma patients may have an increased risk for Down syndrome".…”
Section: Retinoblastomamentioning
confidence: 99%